PENGARUH PELAKSANAAN MODEL PEMBELAJARAN TEMATIK TERINTEGRASI NILAI KARAKTER TERHADAP MINAT BELAJAR SISWA KELAS V SDN 48 BONE-BONE KABUPATEN PANGKEP - irviana, ira; Mahmud, Amrullah (STKIP Andi Matappa Pangkep, 2019)
The purpose of this study were (i) To see the picture of the application of thematic learning model terintegrasinilai character to the interest of students of class V SDN 48 Bone Pangkep district. (ii) To see the picture of class V student interest SDN 48 Pangkep Bone district before and after the integrated thematic learning model character value. (iii) To see the effect of the application of thematic integrated learning model character values to the interest of students of class V SDN 48 Bone Pangkep district.This research is quantitative research type True Experiment Design. The technique of collecting data through questionnaires student interest. The population in this study is the fifth grade students of the school year 2015/2016 The samples in this study were taken from the school SDN 48 Bone ie fifth grade students who totaling 50 people from the large number of the population. Data analysis technique used is descriptive analysis and inferential analysis.The results showed that the application of learning models thematic integrated character value consisting of phase Competency Mapping Basic, stage Establish network theme, stage Develop syllabus, stage menyusunan Lesson Plan (RPP), stage of implementation and Phase evaluation is generally done well based on results and implementation , Student interest in learning in class V SDN 48 Bone regency Pangkep before the application of thematic integrated learning model character values that are in the low category, both in the experimental group and the control group. There is increasing interest in students in the high category in the experimental group after treatment given thematic integrated learning model character values while the control group in the low category. The use of integrated thematic learning model character values affect the interest of students of class V SDN 48 Bone Pangkep district.